Correlation between Body Mass Index and Age at Menarche - Atika Primandina Putri; Yulia Sofiatin; R. M. Ryadi Fadil; Hadyana Sukandar; Nugroho Harry Susanto; Anggraini Widjadjakusuma; Lulu Eva Rakhmilla; Lola Ilona (Althea Medical Journal, 2015)
Background: The decline of age at menarche has been reported in several countries, it occurred because of genetic, ethnic, and socioeconomic improvement in nutritional status and environment. The improvementof nutritional status has occurred globally all over the world including in Indonesia. One of the measuring tools in nutritional status is body mass index (BMI). The objective of the study was to assess the correlationbetween BMI and age at menarche.Methods: A cross-sectional study was carried out among girls aged 9–15 years old in Jatinangor, from May–November 2013. The sample of this study was chosen with cluster random sampling. Age at menarche information was collected through a questionnaire. Body mass index was calculated from measurement of body weight and height. Data was analyzed using Spearman correlation test.Results: Out of three hundred and sixty nine subjects participating in this study, sixty seven were included in the inclusive criteria. According to the classification of BMI of underweight, normal, overweight, andobese, there were 1, 55, 8, and 3 persons, respectively. Mean of BMI was 19.04 and mean age at menarche was 12.72 years, which showed a non significant result (r=-0.013; p= 0.458).Conclusions: Age at menarche was not correlated with BMI. [AMJ.2015;2(4):521–4] DOI: 10.15850/amj.v2n4.656